In silico structure prediction and inhibition mechanism studies of AtHDA14 as revealed by homology modeling, docking, molecular dynamics simulation. (August 2018) - Zhao, Ming-Lang; Wang, Wang; Nie, Hu; Cao, Sha-Sha; Du, Lin-Fang
Graphical abstract: Highlights: The 3D structure of AtHDA14 was constructed using homology modeling. Many common small molecular inhibitors of human HDACs were found also having high binding energy with AtHDA14. Molecular dynamics simulation for representative AtHDAC14-ligand complexes was carried out to further research. MM/PBSA method was used to obtain more valuable information about the residues energy contribution. Abstract: Histone deacetylases (HDACs) play a significant role in the epigenetic mechanism by catalyzing deacetylation of lysine on histone in both animals and plants. HDACs involved in growth, development and response to stresses in plants. Arabidopsis thaliana histone deacetylase 14 (AtHDA14) is found to localize in the mitochondria and chloroplasts, and it involved in photosynthesis and melatonin biosynthesis. However, its mechanism of action was still unknowns so far. Therefore, in this study, we constructed AtHDA14 protein model using homology modeling method, validated using PROCHECK and presented using Ramachandran plots. We also performed virtual screening of AtHDA14 by docking with small molecule drugs and predicted their ADMET properties to select representative inhibitors. MD simulation for representative AtHDA14-ligand complexes was carried out to further research and reveal their stability and inhibition mechanism. Meanwhile, MM/PBSA method was utilized to obtain more valuable information about the residues energy contribution. Moreover, compared with four candidate inhibitors, we also found that compound 645533 and 6918837 might be a more potent AtHDA14 inhibitor than TSA (444732) and SAHA (5311). Therefore, compound 6445533 and 6918837 was anticipated to be a promising drug candidate for inhibition of AtHDA14.